Effects of financial globalization on developing countries: some empirical evidence - Prasad, Eswar et al. (2003)
There has been considerable debate on the relationship between financial development and economic development. While the debate continues, attempts have been made, with the full support of multilateral institutions, to liberalise the financial sector of developing countries. One of the main objectives and responses has been with respect to attracting portfolio capital flows to the so-called emerging markets. Changes were rushed through with hardly any ground work being done. We give in the following the main observations of a recent study by the International Monetary Fund (IMF) which looked at the financial sector changes on developing countries. Interestingly, now IMF cautions the developing countries that "financial integration should be approached cautiously, with good institutions and macroeconomic frameworks viewed as important". - Reproduced.
Keywords: Globalization - Developing countries; Financial administration - Developing countries; Financial administration